Efektivitas Kinerja Dosen Stie Mujahidin Tolitoli Dalam Menggunakan Metode Pembelajaran Daring (Studi Kasus Pada Stie Mujahidin Tolitoli) - suparman stie; Nurliana Nurliana (Economy Deposit Journal (E-DJ), 2020)
The online learning method is a relatively new learning method for the STIE Mujahidin Tolitoli Campus. It needs adjustments. However, that does not mean it is impossible to do. This study aims to determine whether the lecturers' performance of STIE Mujahidin Tolitoli has been effective in using online learning methods. This study uses a qualitative research design. The data source is primary data, namely data obtained through observations, in-depth interviews, and documentation related to this research. The data analysis technique used was data reduction, data presentation (data display), drawing conclusions, and verification of the triangulation technique. The results of research and discussion can be concluded that the performance of lecturers is less effective in using online learning methods. The results showed that the effectiveness indicator was not maximally achieved. Lecturers must enrich themselves with 3M, namely media, methods and materials. Supporting factors for online learning methods must also be improved (facilities and infrastructure, rules made by the campus, increased lecturer competence, and effective and efficient communication between lecturers, and students).